(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2017)
يهدف البحث إلى التعرف على دور التخطيط الاستراتيجي في التعليم العالي الخاص من خلال إبراز مكامن القوة والضعف في الجامعة الخاصة لكي يساعدها ذلك في اختيار الاستراتيجية التي تركزعلى استغلال نقاط القوة لديها وتلافي أو معالجة نقاط الضعف،لكي تتمكن الجامعة الخاصة من استمرارية التطوير والتميز خاصة في ظل الظروف الحالية في سورية . ولقد تم اختيار فرع الأكاديمية العربية للعلوم والتكنولوجيا والنقل البحري في اللاذقية كونها تعتبر من أول الجامعات الخاصة في سورية . ولقد تم الاعتماد على المنهج الوصفي التحليلي واستخدام الاستبيانات لكل أصحاب العلاقة بالتخطيط الاستراتيجي في فرع الأكاديمية وذلك من أجل إبراز الخطوات التي يجب اتباعها لاعداد خطة استراتيجية لفرع الأكاديمية كونها لا تتبع نهج التخطيط الاستراتيجي بشكل عملي على أرض الواقع من أجل تحسين أداء مهامها التعليمية . ومن أهم النتائج التي تم التوصل إليها أن : تفاعل إدارة الأكاديمية مع أدبيات وسلوك التخطيط الاستراتيجي جاء ضعيفاً بسبب ضعف المسؤولية تجاه عملية التغيير وكذلك بسبب التغير المستمر في القيادات الإدارية لفرع الأكاديمية خلال فترات زمنية قصيرة ولأن أعضاء هيئة التدريس ليسوا على علم برسالة الأكاديمية بسبب عدم توفر المناخ الملائم في الأكاديمية حالياً من أجل التغيير والتطوير خاصة في ظل المنافسة القائمة . وفي ضوء هذه النتائج اقترحت الباحثة أنه : يتوجب على إدارة فرع الأكاديمية توفير المناخ اللازم لثقافة التغير من خلال القيام بحملات توعية داخل الاقسام العلمية والإدارية في فرع الأكاديمية لتعريف العاملين برسالة الأكاديمية وأهدافها وخططها المستقبلية . The research aims to identify the role of strategic planning in the private higher education by highlighting the strengths and weaknesses of the private university to help in choosing the strategy to exploit the opportunities and strength points. And also to avoid or address weaknesses and threats. So that the private university would be able to achieve continuous improvements and distinctions epecially in the light of the current circumstances in Syria. And the Academy inLatakia, has been chosen being one of the first private universities in Syria. We relyed on the descriptive and analytical approach and the use of questionnaires for each one who is responsible of strategic planning in the academy in order to highlight the steps to be followed to prepare a strategic plan for the academy because it hasn’t been following the strategic planning approach in a practical way to improve the performance of its educational tasks. The most important results that have been reached are: the academic management interaction with moral and conduct strategic planning was weak due to the weakness of responsibility towards the process of change and also because of the constant change in the administrative leadership of the academy during short periods of time The research has also shown that the faculty teaching members are not aware of the academy’s mission and that is because there isn’t a suitable atmosphere in the academy right now for change and developement especially in the light of the existing competitions. In the light of these results, the researcher suggested the following: The management in this branch should provide the right atmosphere to accept changes by starting awareness campaigns within the scientific and administrative departments of the academy to introduce the members to the mission of the academy, its goals and future plans.